2006
DOI: 10.2298/jsc0607733n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of some Schiff base complexes

Abstract: Two Schiff bases were synthesized from raceacetophenone: 1) ADS1 4-ethyl-6-{(E)-1-[(3-nitrophenyl)imino]ethyl}benzene-1,3-diol and 2) ADS3 4-ethyl-6-[(E)-1-{(2-nitrophenyl)imino]ethyl}benzene-1,3-diol. Then their metal complexes were formed. The metals selected for the preparation of complexes were copper, nickel, iron and zinc. Hence, in total 8 metal complexes were synthesized and screened for antibacterial activity against some clinically important bacteria, such as Pseudomonas aeruginosa, Proteus vulgaris,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 2 publications
1
37
0
Order By: Relevance
“…3d, 3g and 3j were tested as suspensions and their MIC 50 values were still lower than those of their corresponding free ligands. Previous work by Nair et al reported a series of Mn(II) and Cu(II) complexes which exhibited activities lower than the activities of their corresponding free ligands when tested using separately 1,4-dioxane and DMF as solvent [72]. This present study has identified a series of coumarin-derived Schiff bases and their Cu(II) complexes who have displayed good antifungal activity against a clinical strain of C. albicans.…”
Section: Anti-candida Activities Of Schiff Base Ligands and Cu(ii) Comentioning
confidence: 54%
“…3d, 3g and 3j were tested as suspensions and their MIC 50 values were still lower than those of their corresponding free ligands. Previous work by Nair et al reported a series of Mn(II) and Cu(II) complexes which exhibited activities lower than the activities of their corresponding free ligands when tested using separately 1,4-dioxane and DMF as solvent [72]. This present study has identified a series of coumarin-derived Schiff bases and their Cu(II) complexes who have displayed good antifungal activity against a clinical strain of C. albicans.…”
Section: Anti-candida Activities Of Schiff Base Ligands and Cu(ii) Comentioning
confidence: 54%
“…Despite these findings, it is difficult to identify a structure activity relationship (SAR) with respect to electronic and steric properties of a compound. It was found that substitution of a methoxy group (15) in place of ethoxy group (14) had little effect on activity indicating that the bulky nature of the substituent has no effect on the activity of a compound at this position. It may prove difficult to identify a real SAR when the target of the ligands remained unidentified to date.…”
Section: Antimicrobial Activity Of Schiff Base Ligands and Their Coppmentioning
confidence: 99%
“…Transition metal complexes of Schiff bases have attracted a lot of interest due to their potent biological activities such as antifungal, antibacterial, anticancer and herbicidal applications [12][13][14][15][16]. These studies have shown that 0020-1693/$ -see front matter Ó 2010 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…The diameters of inhibition zones were measured after 24-48 hours at 35-37 for bacteria and 3-4 days at [25][26][27] for yeast and fungi of incubation at 28 , with subsequent filtering to remove mycelia fragments before the solution containing the spores was used for inoculation.…”
Section: Growing Of Microorganismsmentioning
confidence: 99%
“…The chemical structure of these molecules is the main factor influencing their thermodynamic aspects. The equivalence between adsorption and micellization tendencies qualifies these surfactants as being applicable in the interfacial applications including emulsification, corrosion inhibition, and biocidal application 26 .…”
Section: Thermodynamics Of Adsorption and Micellizationmentioning
confidence: 99%